Media consumption and civic engagement: the reasoned action theory as a way forward to determine the relationship - Joseph Ramanair, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Communication is important to enable ideas to be transformed into informed actions. As such, the media used for such communication is crucial and play an important role in broadcasting the information. The proliferation of the Internet has greatly enhanced the important role of the media and changed the landscape of the media industry. In addition to conventional media, consumers are now able to access a variety of social media applications. Both types of media are important and needs to be considered as it continues to be consumed across demographics and play important roles in communicating information. Further, both types of media are capable of informing and shaping the views of consumers in a variety of areas from the political to the social. The important question remains as to whether increased availability, access, and connectivity to the various types of media and the information provided have enabled opportunities to media consumers to engage in discussions to stimulate civic engagement leading to activism. Research investigating users’ media consumption and civic engagement with issues explored is largely not well theorised and often offer inconclusive or conflicting results. As such, the ensuing discussion proposes a way forward utilising the Reasoned Action Theory to determine the relationship between media consumption and civic engagement.